OPEN GOVERNMENT: KEY ISSUES IN PHILIPPINES - Afandi, Syed Agung; Erdayani, Rizki; Afandi, Muslim (Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to analyze key issues of open government in the Philippines. This country is one of the eight initiators of the Open Government Partnership. Qualitative approaches and bibliometric analysis methods are used in this study. Data are sourced from Google Scholar and collected using Publish or Perish (using keywords: Philippines transparency, Philippines public participation, and Philippines collaboration). The keywords are based on the main principles of open government. The data selection process and data completion are done using Mendelay, while the bibliometric map is obtained using VOSviewer. This study found 116 relevant articles, 87 topics, 437 total link strengths, and 270 occurrences. The dominant issues are: collaboration, transparency, public participation, accountability, local government, education, governance, economics, health, and extractive industries. At the same time, the latest and potential topics include: democracy, legitimacy, public service, financial reporting, information disclosure, government projects, public bidding, communication, capacity, climate change, health, public work management, disaster management, supply network, women count, sustainable development goals, and judicial consequences. Since its leading role in the OGP, the Philippines has made 75 of its open government commitments and is currently focusing on ten commitments. These commitments have the potential to create a more open Philippine government.